2019
DOI: 10.3390/w11091861
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis and Stochastic Modelling of Hydrological Extremes

Abstract: Analysis of hydrological extremes is challenging due to their rarity and small sample size and the interconnections between different types of extremes and gets further complicated by an untrustworthy representation of meso-scale processes involved in extreme events by coarse spatial and temporal scale models as well as biased or missing observations due to technical difficulties during extreme conditions. The special issue “Statistical Analysis and Stochastic Modelling of Hydrological Extremes”—motivated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Our results suggest wetter winters and drier summers for Belgium, consistent with the results obtained from the CMIP5 GCMs (Tabari et al, 2015). An increase in the length of extreme dry spells (Breinl et al, 2020) and in aridity conditions (Tabari, 2020) was also found for western Europe. The same methodology is followed to assess the significance of the results after downscaling.…”
Section: Significance Of Climate Change Signalssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results suggest wetter winters and drier summers for Belgium, consistent with the results obtained from the CMIP5 GCMs (Tabari et al, 2015). An increase in the length of extreme dry spells (Breinl et al, 2020) and in aridity conditions (Tabari, 2020) was also found for western Europe. The same methodology is followed to assess the significance of the results after downscaling.…”
Section: Significance Of Climate Change Signalssupporting
confidence: 90%
“…convective precipitation). These processes are therefore simplified by means of parameterisation, leading to significant bias and uncertainty in the model (Tabari, 2019). In order to work with these results on finer scales, which is usually required for hydrological impact studies, a downscaling approach can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Mann-Kendall test. The Mann-Kendall statistical test has been frequently utilized to quantify the significance of trends in hydro-meteorological time series (Tabari, 2019;Silva et al, 2015;Duhan and Pandey 2013). The Mann-Kendall (Mann 1945;Kendall 1957) is calculated as:…”
Section: 25mentioning
confidence: 99%
“…To this end, various statistical methods have been developed and used over time. The classical methods, however, rely on many assumptions on the time series to be examined such as normality, temporal and special independency and the temporal constancy of the data distribution [14]. The Mann-Kendall (MK) test is well-known to be non-parametric and therefore not affected by the non-normality of data [15,16] and also because of its low sensitivity to abrupt breaks in inhomogeneous series [17].…”
Section: Introductionmentioning
confidence: 99%